Study of Birth Defects in Basra Governorate Between the Years 2019-2023 - Seiwan, Anwar N. (Journal of Discoveries in Applied and Natural Science, 2025)
The study is a historical one, examining the fact of birth defects during a five-year period, from August 2023 to January 2024, in Basra Governorate. Data for the study were obtained from the Department of Vital Statistics and from the Center for Genetic Blood Diseases within the Health Directorate of Basra from November to December 2023. The study presents a table showing the total number of births in the governorate, live births, cases of birth defects, and incidence of birth defects per 1,000 live births. Another table showed rates and numbers in terms of the top ten etiologies of birth defects, hereditary blood diseases, and other contributing factors. The findings were analyzed by descriptive statistical means, i.e., frequency, percentage, and rate per thousand. The study revealed that the total numbers of births in the governorate were 63,202, 63,091, 60,601, 59,731, and 60,739 within the five-year period ranging from 2019 to 2023.The total number of birth-defect events reported during those years amounts to 195, 262, 231, 331, and 241, thus totaling 1,242 cases of birth defects in five years. The study found that there was a significant increase per annum in births affected by birth defects. It is therefore recommended that the public should be educated on the causes of birth defects and prevention strategies, whereby the health authorities should proceed to establish educational strategies.